Attitudes of nurses and nurse managers towards violence risk assessment and management : A cross-sectional study in psychiatric inpatient settings - Varpula, Jaakko; Ameel, Maria; Lantta, Tella (Wiley-Blackwell, 2025)
Introduction: Workplace violence is a prevalent issue in psychiatric inpatient care. Prevention efforts require the identification of at-risk service users using validated violence risk assessment tools. The shift in violence prevention emphasises preventive measures and collaborative risk assessment together with service users. Nurses have a central role in this process. Therefore, their attitudes are crucial when implementing evidence-based methods.
Aim: To assess the attitudes of nurses and nurse managers towards violence risk assessment and management.
Method: A cross-sectional online survey in Finnish psychiatric inpatient care. Data analysis was conducted with statistical methods. The STROBE guideline was used in reporting.
Results: Nurses (n = 142) valued risk assessment and felt that it was their responsibility. Attitudes towards service users' risk-taking as part of their recovery varied. Nurses had mixed attitudes regarding the effectiveness of risk assessment tools. Older participants and nurse managers had more positive attitudes towards risk assessment tools.
Discussion: The study findings highlight a feeling of responsibility of nurses towards violence risk assessment and at the same time their preference towards their own clinical judgement.
Implications for practice: Understanding nurses' attitudes is crucial in training and implementation processes to address concerns, provide support and enhance positive attitudes.